2011
DOI: 10.1242/jcs.087551
|View full text |Cite
|
Sign up to set email alerts
|

A signaling loop of REST, TSC2 and β-catenin governs proliferation and function of PC12 neural cells

Abstract: SummaryThe RE-1-specific silencing transcription factor (REST or NRSF) is a transcription repressor that orchestrates differentiation and also operates in differentiated neurons and neurosecretory cells (neural cells). Its role in proliferation has been investigated so far only in rapidly growing tumors, with conflicting results: suppression in non-neural tumors, stimulation in medulloblastomas. Working with two clones of chromaffin-neuronal PC12 cells, which express different levels of REST, and using genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 63 publications
(78 reference statements)
3
29
0
Order By: Relevance
“…For transient Rac1 downregulation, the cells, seeded on slides coated with polylysine, were exposed for 48 h to the shRNA (Tomasoni et al, 2001), scrambled or specific. The latter, chosen out of four based on efficacy, was as follows: CGAGGACTCAAGACAGTGTTTGATGAAGC.…”
Section: Methodsmentioning
confidence: 99%
“…For transient Rac1 downregulation, the cells, seeded on slides coated with polylysine, were exposed for 48 h to the shRNA (Tomasoni et al, 2001), scrambled or specific. The latter, chosen out of four based on efficacy, was as follows: CGAGGACTCAAGACAGTGTTTGATGAAGC.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies had shown mTORC1 to be moderately more active, and mTORC2 much less active in the high REST PC12-27 cells compared to the wtPC12 cells (Tomasoni et al, 2011). In order to investigate the possible involvement in these differences of the NGF receptor signaling and of its mTORC1-dependent feed-back inhibition, we analyzed the direct read-outs of mTORC1 and mTORC2, P-S6(S235/236) and P-Akt(S473), respectively.…”
Section: Resultsmentioning
confidence: 97%
“…On the one hand, many neural cell-specific proteins encoded by REST target genes, such as those of regulated neurosecretion, are lacking (D'Alessandro et al, 2008); on the other hand, PC12-27 cells exhibit accelerated cell proliferation, controlled by a signaling loop in which REST operates together with the GAP protein TSC2 and the co-transcription factor β-catenin (Tomasoni et al, 2011). The activities of the two mTOR complexes were found to be dissociated: that of mTORC1 was slightly higher, that of mTORC2 was very low (Tomasoni et al, 2011), much lower than those of wtPC12, of other neural cells and of various types of neurons (Carson et al, 2013; Mazei-Robison et al, 2011; Urbanska et al, 2012). Whether and to what extent these properties of PC12-27 cells depend on their defective NGF signaling had never been established.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is crosstalk between the PI3K/Akt, ERK, and Wnt/β-catenin signaling pathway participating in maintenance of mES cells self-renewal [33,35]. Furthermore, using genetic complementation and knockdown approaches, Tomasoni R et al found that a signaling loop of REST, GTPase-activating protein tuberin (TSC2) and the transcriptional co-factor β-catenin determines proliferation and function of PC12 neural cells [36]. Whether purarin-induced activation of PI3K signaling affects TSC2 and Wnt/β-catenin signaling pathway is still unknown.…”
Section: Discussionmentioning
confidence: 99%